2015
DOI: 10.3389/fmicb.2015.00927
|View full text |Cite
|
Sign up to set email alerts
|

Applying the emergency risk management process to tackle the crisis of antibiotic resistance

Abstract: We advocate that antibiotic resistance be reframed as a disaster risk management problem. Antibiotic-resistant infections represent a risk to life as significant as other commonly occurring natural disasters (e.g., earthquakes). Despite efforts by global health authorities, antibiotic resistance continues to escalate. Therefore, new approaches and expertise are needed to manage the issue. In this perspective we: (1) make a call for the emergency management community to recognize the antibiotic resistance risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…This is in line with the importance of grain filling traits under stress reported in drought conditions (Assefa et al 2013). In LP conditions yield, seed and pod number per area and biomass traits were significantly negatively correlated with DF and DPM, indicating that stress avoidance by early maturity combined with greater physiological efficiency (i.e., more yield per day; Polania et al 2016a) is an important tolerance mechanism. This is again similar to observations in drought stress conditions underlining the similar mechanism for tolerance to these different stress conditions (Beebe et al 2013).…”
Section: Low P Stress Shows Similarities To Drought Stresssupporting
confidence: 85%
See 3 more Smart Citations
“…This is in line with the importance of grain filling traits under stress reported in drought conditions (Assefa et al 2013). In LP conditions yield, seed and pod number per area and biomass traits were significantly negatively correlated with DF and DPM, indicating that stress avoidance by early maturity combined with greater physiological efficiency (i.e., more yield per day; Polania et al 2016a) is an important tolerance mechanism. This is again similar to observations in drought stress conditions underlining the similar mechanism for tolerance to these different stress conditions (Beebe et al 2013).…”
Section: Low P Stress Shows Similarities To Drought Stresssupporting
confidence: 85%
“…Transgressive segregation beyond the parental lines was observed for most traits, indicating promising combinations of parental alleles. Most pronounced positive transgressive segregation was observed for CID where most RILs displayed higher values of CID than the parental lines suggesting higher stomatal conductance and metabolic activity in these lines for effective use of water (Polania et al 2016a).…”
Section: Phenotypic Evaluation Of the Dxg Ril Population In Contrastimentioning
confidence: 96%
See 2 more Smart Citations
“… 19 The WHO also gave a report to examine antibiotic resistance globally in 2014 and held a high level global assembly to call for all countries and regions of the world to take actions to address this urgent problem. 20 QAs were found to be invulnerable to developing antimicrobial resistance in S. mutans and Enterococcus faecalis in vitro . 21 Recently, we found that quaternary ammonium monomers could induce drug resistance in Streptococcus gordonii .…”
Section: Introductionmentioning
confidence: 99%